The Sea Ice Topography of M'Clure Strait in Winter and Summer of 1960 from Submarine Profiles - McLaren, Alfred S.; Wadhams, Peter; Weintraub, Ruth (ARCTIC, 1984)
Submarine profiles of the ice underside in M'Clure Strait were obtained by USS Sargo in February 1960 and by USS Seadragon in August 1960. They gave the first quantitative measurements of the ice draft distribution in the strait and in the nearby Beaufort Sea shelf zone, as well as providing a seasonal comparison of ice conditions within a single year. Analysis of the profiles reveals a region of very high mean ice draft (7.8 m) and heavy ridging off the southwest tip of Prince Patrick Island in winter. Within M'Clure Strait itself the mean ice draft lay in the 4-5 m range and the draft distribution showed that the ice was mainly first-year, as opposed to the mixture of first-and multi-year ice that exists out in the Beaufort Sea. This suggests a local origin for the ice in the strait. Pressure ridges were much more frequent in summer than in winter, as were polynyas. Both the pressure ridge draft distribution (in summer) and the ice draft distribution at great depths (in summer and winter) fitted a negative exponential distribution, in common with other ice profiles which have been analysed.Key words: sea ice, pressure ridges, sonar, M'Clure Strait, Viscount Melville Sound Mots clés: glace de la mer, crêtes de pression, sonar, le détroit M'Clure, le détroit Viscount Melville